Clinical and nursing correlates of severity among chronically ill adults with aspiration pneumonia in Saudi Arabia: A retrospective cross-sectional study - Eman M. Gaber Hassan; Myra Cusi Britiller; Mohammad Daud Ali; May Mohammed Alshowikat; Fatimah Hassan Ahmed Alduhaim; Sarah Mohammad AlOtaibi; Asmahan Shabbab Hamad Al-Mutairi; Hassna Maquta Ali Alharthi; Dalal Sanad Almutairi; Fatimah Saleh Al Awami; Shimaa Mohammed Said (Belitung Nursing Journal, 2026)
Background: Aspiration pneumonia is a major cause of morbidity and mortality in hospitalized adults, yet limited evidence exists from the Eastern region of Saudi Arabia. Objective: To identify clinical correlates of disease severity in patients with confirmed aspiration pneumonia. Methods: A retrospective cross‑sectional study was conducted using medical records of adult patients diagnosed with aspiration pneumonia across two major hospitals in Eastern Saudi Arabia (January 2018 – December 2023). A total of 294 eligible records were reviewed. Demographic, clinical, functional, and respiratory data were extracted. Bivariate and multivariable logistic regression analyses were conducted to identify factors associated with greater clinical severity, defined by respiratory compromise and treatment intensity. Results: The mean age was 63.6 years (SD 24.1); 55.1% were male, and 54.8% were fully dependent. Dysphagia or esophageal dysfunction was common, and nearly half required nasogastric feeding. In the primary multivariable model, lower oxygen saturation (aOR = 0.92, 95% CI 0.85–0.99, p = 0.035), lower Glasgow Coma Scale score (aOR = 0.81, 95% CI 0.68–0.96, p = 0.017), dysphagia/esophageal dysfunction (aOR = 2.72, 95% CI 1.15–6.40, p = 0.022), mechanical ventilation (aOR = 3.42, 95% CI 1.51–7.74, p = 0.003), and broad‑spectrum antibiotic use (aOR = 2.36, 95% CI 1.07–5.18, p = 0.033) were independently associated with greater severity. An exploratory analysis of oral hygiene was limited by sample size. Conclusions: Aspiration pneumonia in Eastern Saudi Arabia predominantly affects older, dependent adults with swallowing impairment. Independent correlates of greater severity include dysphagia, reduced consciousness, hypoxemia, and mechanical ventilation. These findings support routine dysphagia screening, structured oral care, airway protection strategies, and rehabilitative nursing interventions in chronic care pathways for at‑risk patients.